Single-Cell and Single-Nuclei transcriptomics profiling reveals dynamic cellular features in tumor-related adipose microenvironment of breast cancer patients with high BMI - Xiaoxiao Hu; Fang Jia; Lili Li; Wuzhen Chen; Leyi Zhang; Jun Pan; Sangsang Zhu; Zhen Wang; Jian Huang (Translational Oncology)
Objectives: High body mass index (BMI), encompassing overweight and obesity, is a well-established risk factor for developing breast cancer (BC). The underlying mechanisms linking elevated BMI to increased BC risk involve metabolic reprogramming and chronic inflammatory microenvironments regulated by cellular networks within breast white adipose tissue (WAT). However, the complicated landscape and specific cell chat leading to BC-related adipose microenvironment remained unclear. Materials and methods: We unveiled a comprehensive cell atlas by employing single-cell (N = 27) and single-nuclei (N = 6) transcriptomics to address dynamic changes of immune and stromal cell components within WAT in high BMI population. Bulk RNA-seq data sets were used for validation. Results: Characteristics of adipose-infiltrating tissue-resident macrophages (PVMs), APOD+γδ T cells, and mature FKBP5+ adipocytes in breast cancer women with high BMI were revealed, in terms of transcriptional genes, metabolism features, developmental trajectories and gene set enrichment analysis (GSEA). PVMs upregulated c-Maf combined with its co-activator CREB1 to increase TCA cycles. APOD+γδ T cells were found to elevate intracellular lipid metabolism, leading to poor clinical prognosis. Mature FKBP5+adipocytes served as an advanced adipogenesis mediator to promote tumor aggressiveness. In-depth analysis of cell-cell interactions uncovered a remodeling trend towards metabolic dysfunction and chronic inflammation in WAT with weight gain via EGF, CXCL, and CCL signalings. Conclusion: These results provided a novel understanding of detailed and unbiased cellular landscape of WAT in breast cancer with high BMI from single-cell atlas perspective, uncovering interplays between breast adipose-infiltrating immune cells and stromal cells that promote progression of BC under high BMI conditions.